SELNET clinical practice guidelines for bone sarcoma - Blay, Jean-Yves; Kasper, Bernd (Critical reviews in oncology, hematology, 2022)
Bone sarcoma are infrequent diseases, representing < 0.2% of all adult neoplasms. A multidisciplinary management within reference centers for sarcoma, with discussion of the diagnostic and therapeutic strategies within an expert multidisciplinary tumour board, is essential for these patients, given its heterogeneity and low frequency. This approach leads to an improvement in patient’s outcome, as demonstrated in several studies. The Sarcoma European Latin-American Network (SELNET), aims to improve clinical outcome in sarcoma care, with a special focus in Latin-American countries. These Clinical Practice Guidelines (CPG) have been developed and agreed by a multidisciplinary expert group (including medical and radiation oncologist, surgical oncologist, orthopaedic surgeons, radiologist, pathologist, molecular biologist and representatives of patients advocacy groups) of the SELNET consortium, and are conceived to provide the standard approach to diagnosis, treatment and follow-up of bone sarcoma patients in the Latin-American context.
Online verfügbar: 21. April 2022, Artikelversion: 22. April 2022
Gesehen am 27.08.2024